Penggunaan Karbon Aktif Bambu Apus Sebagai Media Penyimpanan Biogas - Krisna Pratama, I Gede; Sucipta, Made; W ijaksana, Hendra (Teknik Desain Mekanika, 2023)
Abstract Simantri was established in every village in Bali to improve the quality of crop production, besides that Simantri also supports the government's efforts to develop renewable energy, namely biogas. Biogas storage at Simantri currently only uses plastic bags with low storage efficiency in storing biogas. One way to increase efficiency in biogas storage is to use activated carbon which acts as an adsorbent. .The objective of this .research. is to. know the ability of activated carbon in biogas storage. Activated carbon is made from apus bamboo using a carbonization temperature of 625? and then activated by the steam activation method with a steam mass flow rate of 50 g/minute. The testing process was carried out by comparing the filling of biogas into empty storage tubes and storage tubes containing 15 grams of activated carbon compressed to a pressure of 100 psi. Empty biogas storage tubes have a storage mass of 30.4 grams, while biogas storage tubes containing activated carbon have a larger storage mass of 39.3 grams for 100 psi pressure biogas. Keywords: Activated carbon, steam activation, biogas storage